Acute Phase Response in Enzootic Bovine Leukosis - GUSEL, M.; TUTUNCU, M.; ALBAYRAK, H.; OZAN, E.; KOC, R.; KADI, H. (Journal of the Hellenic Veterinary Medical Society, 2018)
In the present study, we evaluated acute phase response by detecting haptoglobin (Hp), serum amyloid A (SAA) and fibrinogen in cattle with enzootic bovine leukosis (EBL). A total of 60 Holstein cattle (≤3 years old), comprisingof 40 cattle infected with BLV, and 20 BLV-free healthy controls were enrolled in this study. Diagnosis of the BLV infection was performed by serology (ELISA and AGID) and PCR techniques. APPs were detected by commercial ELISA test kits using validated standard procedures as instructed. All the BLV-infected cattle were in good general health and had normal respiratory rates, pulse rates, body temperatures. However, 5 cattle had enlarged, hard, painless, movable superficial lymph nodes in infected group. APPs including Hp (p<0.001), fibrinogen (p<0.001), and SAA (p<0.05) concentrations were significantly higher in cattle with EBL compared to BLV-free cattle. On hematologic examination, total leukocyte, lymphocyte and granulocytes concentrations were significantly higher in infected cattle when compared tocontrols. In addition, Hp and SAA (p<0. 001) concentrations were significantly higher in symptomatic cattle than asymptomatic. The Pearson correlation revealed significant associations between APPs and total leukocyte and granulocytes; however, there was no correlation with lymphocyte. In conclusion, the results of this study showed increased acute phase response in BLV infected cattle.